The Role of Teacher Personality Competence in Enhancing Students' Resilience and Character at SMP Al-Wasliyah 31 Medan - Khairina, Nadia; Hambali, Usnan; Anggraini, Delima Putri; Syahidah, Syahidah (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study examines the role of teacher personality competence in enhancing students' resilience and character at SMP Al-Wasliyah 31 Medan. Teacher personality competence is an essential factor in shaping students' emotional and psychological development. The research focuses on how teachers' personal qualities, including empathy, communication skills, and emotional intelligence, contribute to fostering a positive learning environment and improving students' resilience. The study employed a qualitative approach with in-depth interviews and observations involving teachers, students, and school management. The findings highlight that teacher personality competence significantly influences students' resilience, self-confidence, and moral development, ultimately contributing to a better learning atmosphere and stronger character formation. This research emphasizes the need for schools to invest in teacher development programs that enhance personal competencies to better support students’ holistic growth.